Pendekatan Sistem Informasi Geografis dan Metode AHP untuk Pemetaan dan Perencanaan Industri Pangan Berbasis Komoditas Utama di Lampung Timur - Izudin, Muhammad Asef; Ridwan, Ridwan; Amien, Elhamida Rezkia; Asmara, Sandi (Jurnal Agricultural Biosystem Engineering, 2024)
East Lampung Regency, located in Lampung Province, holds significant potential for the development of agro-industries based on food crops, particularly corn, rice, and cassava. This study aims to identify the most promising and sustainable agro-industrial commodities using the Geographic Information System (GIS) and Analytical Hierarchy Process (AHP) approaches. The analysis was conducted using spatial and non-spatial data, including land surface temperature (LST), rainfall, soil quality, slope, and land use. The results indicate that corn and cassava have very high land suitability (S1), while rice is moderately suitable (S2). Market factors and pricing are key considerations in selecting the priority commodities. The GIS approach provides informative land suitability maps, while AHP helps establish commodity priorities. The combination of these methods offers a strategic guide for planning and developing sustainable agro-industries in East Lampung Regency. Keywords: ArcGIS, Landsat 8 image, Land Suitability, Potential Featured Commodities.